2005
DOI: 10.1212/01.wnl.0000161871.83614.bb
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for progression of brain atrophy in aging

Abstract: Neurologically asymptomatic elderly experience continuing brain volume loss, which appears to accelerate with age. Glycated hemoglobin A (HbA1c) was identified as a risk factor for a greater rate of brain atrophy. Clustering of factors associated with the so-called metabolic syndrome in subjects with high HbA1c suggests a link between this syndrome and late-life brain tissue loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
289
9
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 373 publications
(334 citation statements)
references
References 39 publications
32
289
9
4
Order By: Relevance
“…24,25 The present results, which demonstrated that marked cerebral atrophy was strongly associated with aging, male sex and WMH, are consistent with those of previous studies. 3,[26][27][28] Several populationbased studies have examined the relationship between cerebral atrophy and cognitive decline. [29][30][31] However, our logistic regression analysis showed no significant correlation between MMSE score and cerebral atrophy.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 The present results, which demonstrated that marked cerebral atrophy was strongly associated with aging, male sex and WMH, are consistent with those of previous studies. 3,[26][27][28] Several populationbased studies have examined the relationship between cerebral atrophy and cognitive decline. [29][30][31] However, our logistic regression analysis showed no significant correlation between MMSE score and cerebral atrophy.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical interpre tation of brain volume loss in patients with MS can be difficult in the context of these other factors. 48 Moreover, differences in the quality and capabilities of MRI hard ware, and in the software packages used for analysis or processing, can generate notable variability in brain atrophy assessments. 32,49 For the above reasons, caution must be exercised when interpreting apparent changes in the rate of brain volume loss.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…Previous crosssectional studies showed no differences in brain volume between subjects with and without MetS (5,6), but high HbA 1c has been identified as a risk factor for a greater rate of brain atrophy over 6 years in a prospective study (7). For the relation of MetS with ischemic stroke, contradictory results have been reported (8)(9)(10)(11)(12), as well as for the relation of MetS with WMH (5,13).…”
mentioning
confidence: 96%